Association of pre-diagnostic vitamin D status with mortality among colorectal cancer patients differs by common, inherited vitamin D-binding protein isoforms - Gibbs, D; Bostick, RM; McCullough, ML; Perez-Cornago, A (Wiley, 2020)
Lower prediagnostic circulating 25-hydroxyvitamin D (25[OH]D)—considered the best marker of total vitamin D exposure—is associated with higher mortality risk among colorectal cancer (CRC) patients. However, it is unknown whether this association differs by the vitamin D-binding protein (GC) isoform Gc2 (encoded by GC rs4588*C>A, Thr436Lys), which may substantially affect vitamin D metabolism and modify associations of 25(OH)D with colorectal neoplasm risk. Prediagnostic 25(OH)D-mortality associations according to Gc2 isoform were estimated using multivariable Cox proportional hazards regression among 1281 CRC cases (635 deaths, 483 from CRC) from two large prospective cohorts conducted in the United States (Cancer Prevention Study-II) and Europe (European Prospective Investigation into Cancer and Nutrition). 25(OH)D measurements were calibrated to a single assay, season standardized, and categorized using Institute of Medicine recommendations (deficient [<30], insufficient [30 - <50], sufficient [≥50 nmol/L]). In the pooled analysis, multivariable-adjusted hazard ratios (HRs) for CRC-specific mortality associated with deficient relative to sufficient 25(OH)D concentrations were 2.24 (95% CI 1.44-3.49) among cases with the Gc2 isoform, and 0.94 (95% CI 0.68-1.22) among cases without Gc2 (Pinteraction = .0002). The corresponding HRs for all-cause mortality were 1.80 (95% CI 1.24-2.60) among those with Gc2, and 1.12 (95% CI 0.84-1.51) among those without Gc2 (Pinteraction = .004). Our findings suggest that the association of prediagnostic vitamin D status with mortality among CRC patients may differ by functional GC isoforms, and patients who inherit the Gc2 isoform (GC rs4588*A) may particularly benefit from higher circulating 25(OH)D for improved CRC prognosis.